Stratégies d’adaptation des communautés rurales à la précarité hydrique dans la commune urbaine de Téra, dans le Liptako Nigérien - Yayé Moussa (VertigO)
This article identifies, analyzes and evaluates the various social adaptation strategies developed by rural communities in the urban commune of Téra, in the Nigerien’s Liptako, to cope with water insecurity. The hydrological, climatic and demographic constraints and the lack of modern water points in the villages lead to a situation of water insecurity to which the communities try to provide social responses. They are thus implementing a variety of strategies (diversification of water supply sources, massive recourse to traditional water points, mixed uses, pooling of water points, et cetera) arranged in a seasonal chronology that allows for the creation of complementarity between villages with different water situations, on the one hand, and on the other hand, between the insufficient number of modern water points and the traditional points that are still at the centre of the rural communities' water supply system. However, with the explosion of needs (population and livestock growth), in a context of global warming, the water problem is likely to deteriorate further because of the pressure on the resource and call into question the social responses contributing to universal access to water. Tensions and conflicts over the resource are likely to appear and develop if political responses in terms of large-scale investment in hydraulic infrastructure is not made in the coming years in rural areas, which seem to be a peripheral territorial category receiving little attention and public action in terms of improving the living conditions of populations and territorial cohesion.